Four years of tax levy on certain financial institutions in Poland – implications for the banking sector - Giżyński, Juliusz (Cztery lata podatku od niektórych instytucji finansowych w Polsce – implikacje dla sektora bankowego, 2021)
The article provides an analysis of the implications for the Polish banking sector regarding the tax on certain financial institutions in Poland, commonly known as the bank levy, in the first four years of the levy’s functioning (2016-2019). The work also indicates the essence of the bank tax as well as the purpose of its collection, including an outline of the legal structure and the resulting risks. Most of the threats posed by the additional levy for the banking sector in Poland have materialized. The most significant negative effects Polish banks suffered in the period under analysis were the decline in profitability, the increase in the prices of banking services, and, consequently, the decline in competitiveness as well as reduced development opportunities. Solutions aimed at increasing the stability of the banking sector, which are particularly important under the conditions of the coronavirus pandemic, have therefore been proposed with regard to the bank tax. During the preparation of the article, the research method used involved the study of literature and analysis of the empirical data published by the most important public (supervisory) institutions in Poland
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 2, s. 33-56